The Mesenchymal–Epithelial Transition During In Vitro Decidualization - Zhang, Xiu-Hong (SAGE Publications, 2013)
The epithelial–mesenchymal transition plays a critical role in embryonic development, cancer progression, and metastasis. Decidualization is the process by which the fibroblast-like endometrial stromal cells differentiate into polygonal epithelial-like cells. However, it is still unclear whether mesenchymal–epithelial transition (MET) occurs during decidualization. The aim of this study was to examine whether decidualization causes the downregulation of some mesenchymal markers and upregulation of some epithelial markers in cultured uterine stromal cells. We showed that decidualization causes the downregulation of snail and vimentin expression, and upregulation of E-cadherin and cytokeratin expression. During in vitro decidualization, cultured stromal cells lose elongated shape and show epithelium-like characteristics. Our data suggest that the process of MET may exist during decidualization.